2015
DOI: 10.15376/biores.10.2.2338-2349
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Low Molecular Weight Chitosan

Abstract: Chitosan can be widely used in many areas owing to its unique properties, although its poor solubility in water is still a limiting factor. In the present study, low molecular weight chitosan (LMWC) was prepared by degradation with NaClO so that chitosan was able to dissolve in water. Chitosan to liquor ratio, NaClO content, temperature, and time were considered variables of NaClO degradation, and the Box-Behnken design was used to determine optimal conditions. There was good agreement between the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“….It has been also reported that sodium hypochlorite (NaClO) can be used to produce chitosan with lower molecular weights or oligochitosan 18 .Among the reagents aforementioned, hydrogen peroxide is more widely used because it is easy to handle, easy to obtain, and more environmentally friendly 4, 13 . In order to effectively and efficiently get oligochitosan, some researchers have combined hydrogen peroxide using microwave irradiation 19,20 , gamma ray radiation 21 , ultraviolet light 22 , ultraviolet-irradiated oxygen 23 , heteropoly acid 24,25 , and ultrasonic 26 .…”
Section: -17mentioning
confidence: 99%
“….It has been also reported that sodium hypochlorite (NaClO) can be used to produce chitosan with lower molecular weights or oligochitosan 18 .Among the reagents aforementioned, hydrogen peroxide is more widely used because it is easy to handle, easy to obtain, and more environmentally friendly 4, 13 . In order to effectively and efficiently get oligochitosan, some researchers have combined hydrogen peroxide using microwave irradiation 19,20 , gamma ray radiation 21 , ultraviolet light 22 , ultraviolet-irradiated oxygen 23 , heteropoly acid 24,25 , and ultrasonic 26 .…”
Section: -17mentioning
confidence: 99%
“…Se ha informado que la masa molar de estos derivados depende de las condiciones de reacción. En tal sentido, ZHENG et al [13] evaluaron el efecto de cuatro variables independientes (relación de quitosano/solución, temperatura, tiempo y cantidad de agente oxidante) sobre la masa molar del derivado sintetizado. Estos autores optimizaron las condiciones operacionales de manera tal de obtener un oligómero de aproximadamente 11000 Da.…”
Section: Figuraunclassified
“…Si bien el valor de la temperatura de degradación máxima de los OQ concuerda con el reportado por ZIEGLER-BOROWSKA et al [22] para quitosano, la temperatura de inicio se desplazó hacia valores significativamente menores. Este resultado puede atribuirse a que el método de degradación oxidativa empleado para la obtención de los OQ alteró la estructura del quitosano, minimizando interacciones intra-e intermoleculares y disminuyendo el peso molecular del polisacárido [13]. El último evento de pérdida de peso corresponde a la destrucción térmica del anillo de piranosa y a la descomposición del residuo carbonoso [20,23].…”
Section: Figuraunclassified
“…Moreover, instead of the unique peak associated to this thermal event in chitosan samples, a broad degradation range is detected in the CO curve. This behavior is based on the fact that oxidative degradation disrupted the chitosan structure by the disintegration of intra-and intermolecular interactions, decreasing the molecular weight of this polysaccharide (Zheng, Yin, Jiang, Xing, & Pu, 2015).…”
Section: Characterization Of Chitosan Oligomersmentioning
confidence: 99%